2020
DOI: 10.31557/apjcp.2020.21.7.1951
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Cervical Cancer and Human Papillomavirus Vaccines among Child-Bearing Aged Women in Hanoi, Vietnam

Abstract: Objectives: The study sought to examine knowledge of cervical cancer and human papillomavirus (HPV) vaccines among child-bearing aged women in Hanoi, Vietnam . Methods: In 2016, 807 women aged 18 to 49 years were recruited from one urban area and one rural area in 2016 and were examined through face-to-face paper-based interviews. Pearson’s chi-square test and an independent t-test were utilized to compare awareness of cervical cancer and HPV vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is particularly important in low-resource countries such as Vietnam, where systematic screening programs for cervical cancer are lacking. A study examining the knowledge of cervical cancer and HPV vaccines among childbearing-aged women in Vietnam revealed an alarming lack of understanding among Vietnamese women [ 22 ]. Therefore, our findings have substantial implications for education curriculum efforts to improve HPV-related knowledge among health science students.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in low-resource countries such as Vietnam, where systematic screening programs for cervical cancer are lacking. A study examining the knowledge of cervical cancer and HPV vaccines among childbearing-aged women in Vietnam revealed an alarming lack of understanding among Vietnamese women [ 22 ]. Therefore, our findings have substantial implications for education curriculum efforts to improve HPV-related knowledge among health science students.…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevention programs are likely to be helpful for early detection of cervical cancer among high-risk groups, which might enhance the provision of effective treatment for precancerous lesions [ 23 ]. Additionally, a greater awareness of cervical cancer among Vietnamese women of reproductive age might have contributed to a slightly declining trend in incidence and mortality of cervical cancer [ 24 ]. Furthermore, improvements in the quantity of medical treatment might have supported early diagnoses and prolonged survival for cervical cancer patients in Vietnam [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of appropriate knowledge, beliefs, and behaviors among individuals regarding cancer prevention contributed to the low proportion of participants in these screening programs [ 9 ]. Although reproductiveage women have a high-level of awareness of cervical cancer, the knowledge of cervical cancer is insufficient among those living in both urban and rural areas [ 24 ]. Thus, health education related to cervical cancer should be provided in order to improve the knowledge of cervical cancer and to promote the uptake of cervical cancer screening among adult women [ 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 A study in Iran revealed that 43% of Medical Sciences students had a positive attitude toward HPV vaccination. 21 In Vietnam, studies related to HPV vaccination have mostly focused on various groups such as parents of boys, 22 mothers with daughters, 23 child-bearing-aged women, 24 and female university students. 16 To the best of our knowledge, no study has specifically targeted health science students in Vietnam.…”
Section: Introductionmentioning
confidence: 99%